Modeling of physical characteristics of heat-accumulating building materials - Yu. S. Yakovleva; A. N. Biryukov (Омский научный вестник, 2023)
The article discusses the results of studies of the physical characteristics of heataccumulating building materials. Modern trends in the production and use of materials determine the need to develop new scientific and methodological devices for assessing the physical characteristics of energy-saving building materials, which will significantly improve the properties of materials, reduce their cost and improve the quality and reliability of structures and products. As such a device, the authors propose the use of a mathematical model, the statistical description of experimental data of which is linear regression. The initial substances for the formation of a microcapsulated heat-accumulating material are selected as input parameters of the system, and the output characteristics are dependent variables (specific heat of the phase transition, compressive strength). Based on the results of experimental studies and using the DataFit program.